(3GbJUGO Gdfbd hGdHjFI aj EWGQ VhGHW GdJfejI GdeSJOGeI (B/s - (3cGaj, eUWai jhSas ((3JdeSGf(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2017)
(3GbJUGO Gdfbd hGdHjFI (B/(3aj GWGQ VhGHW GdJfejI GdeSJOGeI(B/(3eGgjI Gdfbd hJWhQg GdJGQjNj(B/(3GbJUGOjGJ Gdfbd hfXQjGJg(B/(3JNWjW Gdfbd(B/(3Gdfbd GdMVQj (B/(3eaghe GdJfejI GdeSJOGeI hGHYGOgG(B/(3GdHjFI heTcdGJgG(B/(3YdGbI Gdfbd HGdHjFI (B/(3Gdfbd GdMVQj GdeSJOGe GHYGOg hJMOjGJg(B/(3SjGSGJ JNWjW Gdfbd GdMVQj GdeSJOGe (B/(3hSGFd GdehGUdGJ GdYeQGfjI GdeSJOeI s
(3HHdjhZQGajG(B:(3U(B.223s
Keywords: (3GdGbJUGOs; (3Gdfbds; (3Gdfbd(B--(3LhGfH GbJUGOjIs; (3MeGjI GdHjFIs